PENGARUH METODE BERCERITA TERHADAP KREATIVITAS MENGGAMBAR ANAK USIA 5 - 6 TAHUN - Girsang, Mei Lyna; Samosir, Jernih (Fakultas Ilmu Pendidikan Universitas Sari Mutiara Indonesia, 2019)
This study is aimed to determine the effect of the story telling method of drawing creativity children aged 5-6 years in academic year of 2019/2020. Type of the research is descriptive quantitative research. Sample of this research are 20 children in group B TK EL Patisia in academic year of 2019/2020. The technique of collecting the data is documentation and performance of the work. Technic of analyzing the data is technical analysis of the correlation product. Based on the results of the correlation found that r xy = 0.712 ( rhitung> rtabel ) or 0.012> 0.412 with 0 ,05 significance level. It can be concluded that storytelling method affect the students drawing creativity.